E-Curricula: is it embraced or resisted? A case study of Arabic language teachers - Issa khalil alhasanat (Intelektual Pustaka Media Utama, 2019)
This paper represents an investigation into teachers barriers towards the use of E-curricula in teaching Arabic language. It explores questions about the approaches to teaching and the motivations of using E-curricula. The main research method used was semi structured interviews. Many factors were found to influence the use of E-curricula, some of them were surprising and revealing. An unwillingness to challenge or change traditional teaching methods can be assured. These findings contribute to a better-informed appreciation of the state of teaching as well as E-curricula in basic stage schools in Jordan.